1996
DOI: 10.3109/10715769609088044
|View full text |Cite
|
Sign up to set email alerts
|

Altered Levels of Scavenging Enzymes in Embryos Subjected to a Diabetic Environment

Abstract: Maternal diabetes during pregnancy is associated with an increased rate of congenital malformations in the offspring. The exact molecular etiology of the disturbed embryogenesis is unknown, but an involvement of radical oxygen species in the teratological process has been suggested. Oxidative damage presupposes an imbalance between the activity of the free oxygen radicals and the antioxidant defence mechanisms on the cellular level. The aim of the present study was to investigate if maternal diabetes in vivo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…The catalase result for the U embryos is in line with earlier studies showing no differences in mRNA levels between embryos of normal and diabetic U rats (43). Intere s t i n g l y, in the previous study, Mn-SOD tended to be increased in embryos of diabetic rats (43), similar to the result in the present investigation. It may be speculated, therefore, that maternal diabetes could induce a small increase in U-strain mRNA levels of Mn-SOD.…”
Section: Discussionsupporting
confidence: 92%
“…The catalase result for the U embryos is in line with earlier studies showing no differences in mRNA levels between embryos of normal and diabetic U rats (43). Intere s t i n g l y, in the previous study, Mn-SOD tended to be increased in embryos of diabetic rats (43), similar to the result in the present investigation. It may be speculated, therefore, that maternal diabetes could induce a small increase in U-strain mRNA levels of Mn-SOD.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the increase in Mn-SOD, if present, may have been undetected when measured as total SOD activity. This explanation is supported by the studies of Cederberg and colleagues [5,36] showing that the increased activity of SOD in embryos of the malformation-resistant strain, as a result of maternal diabetes, was mainly due to increase in Mn-SOD and not to CuZn-SOD.…”
Section: Discussionmentioning
confidence: 75%
“…The role of oxidative stress as an etiologic factor in diabetic teratogenesis has recently been supported by in vivo and in vitro studies: Forsberg et al [25] found altered levels of scavenging enzymes both in embryos cultured in diabetic conditions and in embryos obtained from diabetic mothers, and different antioxidant agents have been tested with positive results: butylated hydroxytoluene [25,26], vitamin E [27,28], vitamin C [29], and N-acetylcysteine [30].…”
Section: Introductionmentioning
confidence: 99%